Endoscopic Ultrasound-Guided Vascular Therapy: The Present and the Future - Philip S.J. Hall; Christopher Teshima; Gary R. May; Jeffrey D. Mosko (Korean Society of Gastrointestinal Endoscopy, 2017)
Endoscopic ultrasound (EUS) offers access to many intra-abdominal vessels that until now have only been accessible to the surgeon and interventional radiologist. In addition to assisting with diagnostics, this unique access offers the potential for therapeutic intervention for a host of indications. To date, this has had the most clinical impact in the treatment of gastroesophageal varices, with EUS-guided coil and glue application growing in use worldwide. Although randomised controlled trial data is lacking, we discuss the growing body of literature behind EUS-guided therapy in the management of varices. EUS has also been used in specialized centres to assist in non-variceal gastrointestinal bleeding. The treatment of bleeding from Dieulafoy lesions, tumours and pancreatic pseudoaneurysms has all been described. The potential applications of EUS have also extended to the placement of portal vein stents and porto-systemic shunts in animal models. As medicine continues to move to increasingly less invasive interventions, EUS-guided therapies offer substantial promise for the safe and effective delivery of targeted treatment for a widening array of vascular disorders.